Factors affecting students' utilization of learning management system: a case study / Nor Hapiza Mohd Ariffin and Saliza Ramly - Mohd Ariffin, Nor Hapiza; Ramly, Saliza (UiTM Press, 2017)
The advent of e-learning technology has recently made the teaching and learning feasible on the Internet. E-learning is essentially any form of education that is facilitated by the Internet and its technologies used the World Wide Web to support instruction and to deliver course content. The purpose of this paper was to identify the students' utilisation of Learning Management System (LMS) namely, i-Learn at University Teknologi MARA (UiTM). The research examines four factors affecting the utilization of LMS which are technology competency, accessibility of i-Learn, lecturers' initiative and students perceive usefulness toward the utilization of i-Learn. The research employed the quantitative methodology. The respondents are the final year student of computing department at Faculty of Computer and Mathematical Sciences. Findings revealed that the level of utilization of i- Learn features is acceptable where score (Mean=2.94). Thus, the highest mean refers to technology competency (Mean = 3.16) followed by lecturers' initiative (Mean = 3.10), students' access to i-Learn (Mean = 3.00) and the lowest is students perceive usefulness toward utilization of i-Learn (Mean = 2.89). This studies also showed the correlation between factors affecting the utilization of i-Learn with theutilizationofi-Learnfeatures. Four hypotheses were analysed and tested where three were accepted and one was rejected. The result showed that "equationeditor"and develop content within i-Learnare preferred as an additional tool, contributed as the highest mean (Mean = 3.05) and (Mean = 3.04) respectively. Finally, recommendations for future improvements of LMS were also discussed. In line with the current educational situation, this study findings can be guidelines for other universities that practiced web-based learning to improve the existing learning management system.